The First Results of a Full Loading Dose of Brolucizumab in the Treatment of DME - R. N. Amirkulieva; E. N. Khomyakova; I. A. Loskutov (Oftalʹmologiâ, 2023)
The aim of the study was to evaluate the efficacy and safety of brolucizumab in the Russian population of patients with diabetic macular edema. Patients and methods: 41 patients (29 women and 12 men) with diabetic retinopathy and diabetic macular edema of comparable age were included in the study. The patients were divided into 2 groups depending on the previous DME treatment. The first group included 24 patients (24 eyes) who had not previously received treatment: 9 men and 15 women, the average age of patients was 62.9 ± 9.3 years, the average best-corrected visual acuity was 0.40 ± 0.23, CTS 332 ± 87 microns, MV 9.65 ± 1.2 mm3. There were 17 patients (17 eyes) in the second group, they had previously received other antiangiogenic drugs, but retained the activity of the disease against the background of the treatment (1 man and 16 women), the average age of patients was 60.6 ± 8.3 years, the average best-corrected visual acuity was 0.40 ± 0.27, CTS 351.6 ± 149.0 microns, MV 9.3 ± 1.8 mm3. All patients received at least 5 intravitreal injections of brolucizumab (205 injections in total) at intervals of 6 weeks. The control examination was carried out 6 weeks after the last injection and a month after the fifth injection. The best-corrected visual acuity, intraocular pressure, central retinal thickness (CTS), macular volume (MV) were evaluated according to optical coherence tomography. Results. In the first group, a statistically significant increase in the best-corrected visual acuity was revealed from 0.40 ± 0.23 to 0.575 ± 0.27 (p = 0.05), the indicators of CTS and MV statistically significantly decreased. In the second group, only a decrease in CTS was detected, while the indicators of BCVA and MV did not show statistically significant changes. Conclusion. Patients with DME, who were treated with brolucizumab and who had not previously received treatment with other drugs, showed an improvement in anatomical and functional parameters, patients, who retained the activity of the disease against the background of the treatment, showed a slight decrease in the activity of the disease.